Examining the Principle of Ignorantia Facti Excusat, Ignorantia Iuris Non Excusat In the Corruption Case Nizzadro Fabio - Asa, Simplexius (Indonesia Law Review, 2023)
This study was designed as a normative research based on documentary research while the data is analyzed based on the court decisions and is presented in a qualitative descriptive manner, aiming to find out the essential meaning of the teachings of ignorantia facti excusat, ignorantia iuris non excusat, and to knowing the implementation of the principles of ignorantia facti excusat, ignorantia iuris non excusat. This is in the regulations and judicial practice in Indonesia through the views of the judges in decision Number 20/Pid.Sus-TPK/2022/PN. Kpg. The study found three main conclusions, namely first, the principle of ignorantia facti excusat, ignorantia iuris non excusat is discussed and examined within the framework of criminal responsibility which is inseparable from guilt. Secondly, in Indonesia, differences in legal treatment in terms of ignorance of facts and ignorance of the law are always explained in relation to mens rea or mental elements which are distinguished on two main points, namely intentionality and negligence. Deliberateness is further divided into three aspects, namely deliberately as an intention, deliberately as a certainty, and intentionality as a possibility. Third, in decision Number 20/Pid.Sus-TPK/2022/PN.Kpg., the principle of ignorantia facti excusat, ignorantia iuris non excusat is linked to unlawful nature and/or intentional elements as the main elements of Articles 2 and 3 of the Act Corruption Crime. In the judge's decision which was used as legal material in this study, the indictment was declared legally and convincingly not proven so that the defendant NF was acquitted.